View from the Past – the Way to the Future - M. V. Melnik (Управление)
This article describes the main developments and results of the emergence, formation and development of the scientific school of management theory. The article estimated place, role, contribution of the scientific school of State University of Management to the improvement and development of the theory and practice of management of the national economy of Russia.